The electroanalytical applications of carbon nanotube-modified electrodes - Keeley, Gareth (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
In this study, cyclic voltammetry, potential step chronoamperometry, batch amperometry, hydrodynamic voltammetry and electrochemical impedance spectroscopy were used to investigate the physical and chemical properties of glassy carbon macro-electrodes modified using HiPCo® single-walled carbon nanotubes. The latter were themselves characterised using atomic force microscopy, infrared and Raman spectroscopy and thermo-gravimetric analysis. The electrochemistry of redox-active functionalities present on the nanotube surface was probed. The modified electrodes were used to determine ferrocyanide, dopamine, epinephrine, norepinephrine, ascorbic acid, NADH, oxygen and hydrogen peroxide. Comparisons between the electro-catalytic properties of nanotubes and conventional graphite were also performed. The suitability of a number of different solvents for the dispersion and casting of nanotubes was evaluated.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin